Phenotypic and Transcriptomic Analysis Revealed a Lack of Risk Perception by Native Tadpoles Toward Novel Non‐Native Fish - Yuanfei Wang; Yudong Zhu; Liuyang He; Haoqi Yu; Xiuqin Lin; Jianghong Ran; Feng Xie (Ecology and Evolution)
ABSTRACT The introduction of alien species poses a serious threat to native biodiversity, and mountain lake systems in the southwest of China are particularly vulnerable to the introduction of non‐native fish. The prey naivety hypothesis states that native species may not be able to recognize novel introduced species due to a lack of common evolutionary background and therefore become easy targets, so the impacts of non‐native fish on mountain endemic amphibians need to be urgently assessed. In an ex‐situ experiment, we exposed the tadpoles of the Chaochiao Brown Frog (Rana chaochiaoensis), endemic to western China, to kairomones of both native and translocated fish species, and their phenotypic and genetic response patterns were compared. The results revealed significant phenotypic plasticity responses in total length (TOL), tail length (TL), and tail muscle width (TW) of tadpoles induced by native fish kairomone, while tadpoles exposed to translocated fish kairomone exhibited weaker phenotypic changes. At the transcriptional level, the number of differently expressed genes (DEGs) in the native fish treatment was 3.1‐fold (liver) and 52.6‐fold (tail muscle) higher than in the translocated fish treatment, respectively. There were more unique DEGs in the native fish treatment, primarily enriched in terms and pathways related to stress response, energy metabolism, and muscle development. The study revealed a lack of risk perception by native tadpoles toward novel non‐native fish, providing new evidence for the prey naivety hypothesis from both phenotypic and molecular perspectives. Future conservation efforts should prioritize assessing the impacts of non‐native fish on alpine and subalpine threatened and narrowly distributed amphibians. Additionally, prevention, early warning, monitoring, and removal of non‐native fish should be carried out as soon as possible.